2017
DOI: 10.1080/0142159x.2017.1296564
|View full text |Cite
|
Sign up to set email alerts
|

A case-based medical curriculum for the 21st century: The use of innovative approaches in designing and developing a case on mental health

Abstract: The introduction of case-based learning (CBL) by the School of Medicine at Cardiff University has encouraged innovation in medical teaching and learning. During years one and two of the modernized MBBCh program, students complete 17 cases as part of the newly developed C21 curriculum that emphasizes a patient-oriented and student-centered approach to learning. The mental health case, which is presented in year 2, incorporates a number of novel teaching resources that aim to enhance the students' learning exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 12 publications
2
24
0
4
Order By: Relevance
“…Our study showed positive acceptability of our new MMI station by the candidates. The candidates reported overall satisfaction with the use of video in the MMI and they agreed it was authentic and interesting, which concurs with that observed in other studies that used videos in PBL or CBL settings [22][23][24][25][26] Furthermore, the candidates did not differ in terms of their perceptions of the video-based case and of the patient-doctor relationship depicted in the video with respect to age, gender, geographic or undergraduate backgrounds. In addition, candidates' performance at the video-based MMI station did not differ with respect to their demographics or backgrounds.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study showed positive acceptability of our new MMI station by the candidates. The candidates reported overall satisfaction with the use of video in the MMI and they agreed it was authentic and interesting, which concurs with that observed in other studies that used videos in PBL or CBL settings [22][23][24][25][26] Furthermore, the candidates did not differ in terms of their perceptions of the video-based case and of the patient-doctor relationship depicted in the video with respect to age, gender, geographic or undergraduate backgrounds. In addition, candidates' performance at the video-based MMI station did not differ with respect to their demographics or backgrounds.…”
Section: Discussionsupporting
confidence: 86%
“…The use of videos to present cases or problems has been studied in case-based learning (CBL) and problem-based learning (PBL) situations, and these studies have shown video-based CBL and PBL are more effective than using paper-based alternatives in terms of fostering critical thinking and interest, and thus, it has been speculated video-based case presentation provides students with more authentic contexts and enhances interest and engagement [22][23][24][25][26]. Yet, little research has been undertaken on the use of video to asses candidate non-academic attributes in MMIs.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we chose paper and video cases because of high feasibility and popularity of these modalities; however, it would be necessary to conduct further research to compare new modalities, such as e-CBL [38,39] and simulation-based scenarios [40].…”
Section: Pedagogical Implications Of Using Different Modalities To Immentioning
confidence: 99%
“…With respect to the micro-lm making, students were required to present a case story containing both clinical factors, such as pathogenesis, diagnosis, and treatment, and related social medicine factors, such as poverty and humanism, sexual discrimination, and doctor-patient relationships. Students were encouraged to discuss these factors in a focus group under CBL structured questioning guidelines provided by the teacher [25].…”
Section: Experimental Group (Mf+cbl Model) Designmentioning
confidence: 99%